1992
DOI: 10.1172/jci116069
|View full text |Cite
|
Sign up to set email alerts
|

Distinct sites of production and deposition of the putative cell death marker clusterin in the human thymus.

Abstract: Clusterin is a multifunctional protein endowed with cell-aggregating, complement-inhibitory, and lipid-binding properties. Since several studies have demonstrated highly increased clusterin gene expression in epithelial and nervous tissues regressing as a consequence of tissue involution and apoptotic cell death, clusterin is also considered as a specific marker of dying cells. To determine whether clusterin expression is also upregulated during thymocyte death occurring during the negative selection process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 53 publications
2
26
1
Order By: Relevance
“…In situ hybridization studies have localized expression of clusterin mRNA to thymic medullary epithelial cells, 21 and our immunohistochemical studies confirm this in neoplastic thymic epithelium. Spindle cell thymomas share many histologic features with follicular dendritic cell tumors, including nodules or whorls of spindled cells with vesicular nuclei, perivascular spaces, and intermixed lymphocytes.…”
Section: Discussionsupporting
confidence: 73%
“…In situ hybridization studies have localized expression of clusterin mRNA to thymic medullary epithelial cells, 21 and our immunohistochemical studies confirm this in neoplastic thymic epithelium. Spindle cell thymomas share many histologic features with follicular dendritic cell tumors, including nodules or whorls of spindled cells with vesicular nuclei, perivascular spaces, and intermixed lymphocytes.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, neither a cell death protective nor an apoptosis-promoting role of clusterin could be assigned based upon the current observations. This is actually in contradiction to some previous results, where alterations in clusterin ex-pression were observed upon induction of apoptosis [11], [16]. A possible explanation for this discrepancy might be differences in the condition of delivering cell death-inducing signals, since it has been also previously reported that the quality of the cell death inducing signal can differently regulate and affect clusterin expression under apoptotic conditions [25].…”
contrasting
confidence: 98%
“…Also tumor cells were identified as source of increased clusterin expression, which was considered as a result of the apoptotic processes [13]. In contrast, other groups have reported a lack of evidence for clusterin expression in apoptotic thymocytes [14], [15] while others have shown that, not apoptotic cells themselves but rather, bystander cells surviving the apoptotic process might be the source of clusterin production [16] [16]. In addition to these reports, contradictory observations on the role of clusterin in both protecting [17] and promoting apoptosis [18] have been reported; therefore the biological function of clusterin during apoptosis is indeed confusing and conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…7,8) In recent studies, however, clusterin up-regulation has been shown to be dissociated from apoptosis. 9,10) We also demonstrated the antiapoptotic activity of clusterin against androgen ablation and cytotoxic chemotherapy using several kinds of prostate cancer models. [11][12][13][14] In the kidney, up-regulation of clusterin expression has been shown to protect renal tissue from apoptosis induced by several kinds of stimuli, including urinary tract obstruction and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Recent studies, however, have provided conflicting findings regarding the relationship between up-regulated clusterin expression and increased apoptotic activity. 9,10) Recently, we also demonstrated the powerful antiapoptotic activity of clusterin using several kinds of prostate cancer models; that is, increase in clusterin expression after androgen withdrawal stimulates tumor progression by inhibiting castration-and chemotherapy-induced apoptosis. [11][12][13][14] Despite the finding by Parczyk et al that clusterin mRNA is 3-fold overexpressed in tumor tissues compared with adjacent normal tissue, 15) the functional significance of clusterin expression in RCC has not been well characterized.…”
Section: Introduction Of Clusterin Gene Into Human Renal Cell Carcinomentioning
confidence: 99%